Effects of implant threads on the contact area and stress distribution of marginal bone - Chia-Ching Lee; Shang-Chih Lin; Ming-Jen Kang; Shu-Wei Wu; Ping-Yuen Fu (Elsevier, 2010)
Stable osseointegration between implant threads and the surrounding marginal bone provides the mechanical base of an implant for daily chewing activity. The contact area of implant-bone interfaces and the concentrated stresses on the marginal bones are principal concerns of implant designers. The purpose of this study was to investigate the effects of thread shape and taper on the initial stability of the implant-bone structure. Materials and methods: The thread design was parameterized by shape and taper. Thread shapes included symmetrical, square, and buttressed. Thread tapers were divided into cylindrical and conical profiles. Nine variations of the thread design were developed to numerically evaluate their geometric and mechanical effects on the marginal bone. Results: Among the three thread shapes with the same pitch, the contact area of the square thread was the highest. Among all implant models, it was found that the site with the greatest stress in the surrounding jaw bone was consistently concentrated at the root radii of the first thread. The maximal stress of the square thread was the least. For the same thread shape and taper, a finer pitch resulted in a remarkable increase in the contact area and a decrease in the peak stress. The contact areas and peak stresses of the conical and cylindrical implants were nearly equal. Conclusion: Taking wall thickness and stress concentrations into consideration, the square thread with a 0.60-mm pitch possessed the optimal contact area and stress values compared to the others.